Cost-Related medication non-adherence in Pakistan: a pervasive public health challenge - Iqbal Khan, Muhammad Fahad; Shah, Izhar Muhammad; Khan, Shahzaib (Journal of the Pakistan Medical Association, 2025)
Madam, Cost-related medication non-adherence (CRMNA) refers to failing to adhere to a prescribed medication regimen due to financial constraints. Predictors for CRMNA include high out-of-pocket medication costs, limited financial resources, lack of medication insurance, younger age, and poorer overall health.(1) Being one of the major determinants of non-adherence, CRMNA remains a significant barrier to effective treatment for patients in many countries, especially in developing countries like Pakistan. This is because, unlike developed nations with robust healthcare systems and widespread health insurance coverage, Pakistan relies heavily on out-of-pocket spending for medications. A recent study conducted in Pakistan found high medication costs to be a major cause of non-adherence to medication, with 92.7% of the patients’ responses reporting it as a factor.(2) Non-adherence to medication reduces the effectiveness of the recommended treatment and therefore leads to disease progression, lower quality of life, and even death. Furthermore, non-adherence substantially increases the financial burden on the healthcare system by increasing the use of resources such as nursing homes, emergency services, hospital admissions, etc.(3) In this way, CRMNA creates a crippling cycle: As patients skip medications due to the high cost, their conditions worsen, leading to more expensive interventions, which subsequently further inflate medication costs. This is especially problematic for Lower Middle Income Countries (LMIC) such as Pakistan where the situation is further compounded by a healthcare system riddled with limitations including insufficient financing, weak healthcare infrastructure and a limited healthcare workforce. The introduction of the ‘Sehat Sahulat Program’ (SSP) in 2015 in Pakistan was a remarkable step towards Universal Health Coverage (UHC), an initiative by the World Health Organization (WHO), which aims to provide essential healthcare facilities to everyone protecting them from out-of-pocket health expenditures. However, since the program does not cover OPD facilities, it still does not solve the serious problem of CRMNA.(4) Breaking the cycle of CRMNA necessitates a multi-pronged approach. Physicians should be encouraged to practice cost-conscious prescribing which may involve promoting the use of generic medications and considering the overall cost of treatment plans for patients. Government intervention is crucial to regulate drug pricing and foster competition within the pharmaceutical market. To improve access, public health insurance should fully cover or significantly subsidize essential medications. By proactively addressing CRMNA and prioritizing affordable healthcare solutions, we can pave the way for a healthier and more prosperous future for all Pakistanis.